Human otoacariasis caused by Amblyomma testudinarium: Diagnosis and management. Issue 26 (June 2017) - Nakao, Yoshio; Tanigawa, Tohru; Shibata, Rei
Abstract: Rationale: Tick infestation of the external auditory canal (EAC) constitutes <1% of all patients presenting with ear complaints. Consequently, parameters for the diagnosis and management of ticks in the EAC have not been established. Patient concerns: We report 2 cases of EAC infestation by Amblyomma testudinarium in 2 female patients, aged 12- and 72 years old. Diagnoses interventions and outcomes: In both patients, otoscopic examination revealed engorged ticks attached to the ear canal. The 12-year-old girl had a narrow EAC, necessitating slight dislodging of the tick to determine if its mouth parts were embedded in the EAC skin. The tick's mouth parts were confirmed to be free, enabling complete removal of the tick. The 72-year-old woman had a wide EAC, enabling tick removal using Hartman's forceps because the tick's mouth parts were confirmed to be free of the skin. Prophylactic tetracycline (200 mg/day) was administered to each patient for 7 days; neither showed any signs of fever or rash. Lessons: This report describes 2 patients with A testudinarium infestation of the EAC, and proposes a simple, noninvasive protocol for determining if the tick is anchored to the ear canal.